Primer on the Pathogenesis of Severe COVID-19: Part Two - Thomas J. Walsh (European Medical Journal, 2020)
In the following continuation article, the author will expand on how the mechanisms discussed in Part One capitalise on host characteristics to produce the organ specific damage seen in severe coronavirus disease (COVID-19), with specific reference to pulmonary and cardiac manifestations. Pneumonia is the primary manifestation of COVID-19; presentation varies from a mild, self-limiting pneumonitis to a fulminant and progressive respiratory failure. Features of disease severity tend to directly correlate with patient age, with elderly populations faring poorest. Advancing age parallels an increasingly pro-oxidative pulmonary milieu, a consequence of increasing host expression of phospholipase A2 Group IID. Virally induced expression of NADPH oxidase intensifies this pro-oxidant environment. The virus avails of the host response by exploiting caveolin-1 to assist in disabling host defenses and adopting a glycolytic metabolic pathway to self-replicate. Although not a cardiotropic virus, severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) can induce arrhythmias, a myocarditis-like syndrome, and myocardial infarction. Monocyte activation as a consequence of a surge of cytokine expression is the driver of these processes. Induced expression of cluster of differentiation 147 (CD147) and TNF-α may also have a role. SARS-CoV-2 fluently harnesses the immune mechanisms of the host to its advantage, rendering it a formidable systemic pathogen. Future effective treatments are contingent upon improved aetiological understanding.